Coping with Cervical Cancer in Adolescence: a Look from Psychology - Laura Naranjo Hernández; Janet Villafuerte Reinante; Aymara Rodríguez Márquez (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Cancer has diverse effects on adolescent health. Facing the diagnosis is difficult, suffering from this disease opens the door to important changes in self-image, future prospects, daily routines, in addition to the devastating effects on the health of the adolescent and the family. The most frequent reactions are: fear, sadness, anger and uncertainty. Coping with the problem with integrity, affective regulation appearing normal, adaptation to action, calm, search for information and social support, reappraisal or cognitive restructuring and distraction are coping strategies suggested for coping with the disease. The intervention of psychology as a specialty allows clarifying, mediating and alleviating the pain of patients and families, it is essential, since it deals with the emotional responses of patients, their families and the medical team.